Penerapan Media Pembelajaran Aplikasi Animaker untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 3 Lajer - Firda Fauziah Rakhmah; Susilawati Susilawati; Erna Labudasari (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Words According to Fatakh (2010) the word "media" comes from the Latin medius which literally means middle, intermediary or introduction. Media is something that delivers or forwards information or messages between the source (message giver) and the message recipient. According to Blake and Horalsen: "Media is a communication channel or medium used to carry or convey messages, where this medium is a road/traffic for messages between the communicator and the communicant, which is deliberately created and occurs in a class together. Planning the learning media for the Animaker application uses several designs including using a Learning Implementation Plan (RPP), Application of the Animaker application learning media is carried out in two cycles, each cycle consisting of one meetings and each cycle consists of four components, namely: planning, action, observation, and reflection. Learning outcomes in science subjects on the water cycle and natural events using the Animaker application learning media only showed an increase of 37% in cycle I. Learning outcomes of the Animaker application learning media to improve class V learning outcomes at SDN 3 Lajer with Natural Sciences (Science) subjects. Theme 8 subtheme 1 Water Cycle and Events in class V students of SDN 3 Lajer, Tukdana District, Indramayu Regency after carrying out pre-cycle actions, cycle I and cycle II experienced an increase and exceeded the research target, namely 82%.